What Explains the Low Survival Rate of Developing Country Export Flows? - Brenton, Paul; Saborowski, Christian; von Uexkull, Erik (World Bank, 2013)
Successful export growth and diversification require not only entry into new export products and markets but also the survival and growth of export flows. For a cross-country dataset of product-level bilateral export flows, exporting is found to be a perilous activity, especially in low-income countries. Unobserved individual heterogeneity in product-level export flow data prevails even when a wide range of observed country and product characteristics are controlled for. This questions previous studies that used the Cox proportional hazards model to analyze export survival. Following Meyer (1990), a Prentice-Gloeckler (1978) model is estimated, amended with a gamma mixture distribution summarizing unobserved individual heterogeneity. The empirical results confirm the significance of a range of product- as well as country-specific factors in determining the survival of new export flows. Important for policymaking is the finding of the value of learning-by-doing for export survival: experience with exporting the same product to other markets or different products to the same market is found to strongly increase the chance of export survival. A better understanding of such learning effects could substantially improve the effectiveness of export promotion strategies.